An educational needs analysis of sustainable dietary education for nutrition teachers: an application of the IPA, Borich needs assessment and The locus for focus model - Eunseo Yang; Borham Yoon (Korean Journal of Community Nutrition)
Objectives This study aimed to investigate the importance and performance levels of sustainable dietary education across the health, environment, and society domains as perceived by nutrition teachers and evaluate the needs and priorities for sustainable dietary education. Methods An online survey was conducted for 151 nutrition teachers in Jeollanam-do. The survey included 20 questions across the health, environment, and society domains. The data were analyzed using a paired-sample t-test, the importance-performance analysis (IPA), the Borich needs assessment, and The locus for focus model. Results Overall, the average importance levels of the 20 items of sustainable dietary education were significantly higher than their average performance levels (4.44 vs. 3.68). The examination of each educational domain revealed that although the importance of education in the health domain was recognized and actively practiced by the nutrition teachers, the performance was comparatively lower in the environment and society domains. The Borich needs assessment and the locus for focus model identified education on biodiversity conservation, plant-based protein, and the use of local food as the top-priority group in the environment domain along with fair and ethical food, food security, regional food culture, food policy and trade, and family dining culture as the second-priority group in the society domain. Conclusion The results of this study underscore the need to support the nutrition teachers’ perception and practice of sustainable dietary education in the environment and society domains. We believe that the educational needs and priorities proposed in this study will be considered in the future development and modification of sustainable dietary education programs.